Fundamentals of Voice and Articulation - Mayer L. V. (Boston McGraw Hill, 1996)
For over 40 years Fundamentals of Voice and Articulation has successfully assisted a wide range of audiences from voice professionals to nonnative English speakers. Youll enjoy Lyle V. Mayers lively and often humorous approach to this subject as he strives to make improving your speech and voice an enjoyable and effective experience.
Keywords: 811.111